The case of transition economies: what institutions matter for growth? - Azim Raimbaev (Economics and Econometrics Research Institute (EERI), 2011)
There is a consensus among scholars that institutions (i.e. norms and regulations) are country specific. The paper aims to contribute to the debate by examining the type of institutions which have been the most important for growth in transition countries. It employs a new set of the institutional variables published by the World Bank against the commonly used transition index of the European Bank for Reconstruction and Development. Also, the paper tests the validity of some arguments presented in the institutional literature. As a result, it appears that among the institutional variables government effectiveness has the most significant impact on economic development of the former planned economies. However, at this stage, the classical growth factors such as investment and export turn out to be more important for growth than institutions.
Keywords: O43; P21; P36; 330; Institutions; governance; transition economies; growth